Inovasi beras semar: Alternatif beras analog untuk manajemen glikemik bagi pasien diabetes melitus - Arina Tina Salwa; Arina Rihadatulaisy Sabila; Afifah Salsabila; Arwani Arwani; Shobirun Shobirun; Suharto Suharto (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Diabetes mellitus is a non-communicable disease with increasing prevalence. Diabetes management through diet is a challenge, especially due to limited safe and nutritious food options. Semar Rice was developed as a solution to provide healthy food alternatives for people with diabetes.Objectives: The purpose of this research is to create an innovative food product in the form of analog rice from a combination of purple sweet potato, cinnamon, and milkfish bones as an alternative food for people with diabetes mellitus.Methods: This study used Research and Development method with laboratory testing for nutritional analysis. The research was conducted at the Food Nutrition and Health Laboratory of XYZ University from January to March 2024. Organoleptic tests were conducted on 10 healthy respondents aged 20-23 years. Three formulations were tested, namely A (35:35:30), B (60:20:20), and C (40:30:30). The glycemic index was tested by measuring the respondents' blood glucose response after consumption of 100 grams of Semar Rice compared to white rice.Results: Laboratory test results showed that sample A contained 56.88% carbohydrate, 6.03% fat, 12.26% protein, 2.82% glucose, and 3.35% sucrose. Semar rice with a portion of 297.4 grams had a glycemic index of 82.20 and a glycemic load of 49.78, although there were variations in results because some respondents did not follow the blood sugar check procedure. The organoleptic test showed a score of aroma 3, taste and texture 3.1, and color 3.5. Semar rice also meets SNI 6128-2015 standards for moisture and carbohydrate content.Conclusion: The conclusion of this study showed that Beras Semar has a low index glycemic compared to white rice. After doing Index Glycemic Test to 10 respondents, the result appear if the respondent’s glucose level more stable after consume Beras Semar than White Rice. KeywordsAnalog rice, diabetes mellitus, alternative food